Enhanced Recovery in Thoracic Surgery: A Review - Dinic, Vesna D.; Stojanovic, Milena Dragisa; Markovic, Danica; Cvetanovic, Vladan; Vukovic, Anita Zoran; Jankovic, Radmilo J. (Frontiers in Medicine, 2018)
Abstract The main goal of enhanced recovery program after thoracic surgery is to minimize stress response, reduce postoperative pulmonary complications and improve patient outcome, which will in addition decrease hospital stay and reduce hospital costs. As minimally invasive technique, video-assisted thoracoscopic surgery (VATS) represents an important element of enhanced recovery program in thoracic surgery. Anesthetic management during preoperative, intraoperative and postoperative period is essential for the enhanced recovery. In the era of enhanced recovery protocols, nonintubated thoracoscopic procedures present a step forward. This article focuses on the key elements of the enhanced recovery program in thoracic surgery. Having reviewed recent literature the authors highlight potential procedures and techniques that might be incorporated into the program. Keywords: enhanced recovery, thoracic surgery, VATS, ERAS, thoracic anesthesia